PHYTOCHEMICALS, BIOACTIVITIES AND THERAPEUTIC APPLICATION OF THREE MEDICINAL PLANTS OF SINDH, PAKISTAN: IPOMOEA CARNEA, TINOSPORA MALABARICA, FAGONIA INDICA (The Research of Medical Science Review, 2024)
Research outcomes on the effectiveness and safety of existing and newly produced drugs recommend naturally produced therapeutic constituents due to safety and the least side effects. Hence, millions of researchers continuously explore medicinal plants to isolate known and new compounds and formulate safe therapeutics. Literature expands daily, covering such studies which need to be reviewed for summary, comparative survey and especially to present gapes suggested in previous studies which may be direction for future work and getting more out of species that still have potential for further scientific research work. In this context, three species of medicinal plants of Sindh origin, Pakistan, have been selected for this review.Ipomoea Carnea: This plant has been chosen by folk medicine experts and is used as a raw material for Unani medicine. As per available literature, toxic effects were initially evaluated, followed by chemical exploration, and to some extent, its safety profile was also assessed.Fagonia Indica: Many varieties of Fagonia are commonly found throughout Pakistan, parts of India, and the Middle East. In the Sindh region of Pakistan, Indica is the most commonly found species of Fagonia, known as “Sachi Booti” that means true herb (Ali et al. 2021). Local medicinal uses are also reported which include treatment of cancer and issues caused due to any poisonous substances. Different compound have been isolated and bioactivity studies are also reported. Tinospora Malabarica: Species of the genus Tinospora are very close to each other; however, their difference from a botanical point of view and chemical profile is quite different and reported in literature. Various papers have reported the use of this plant as a source of therapeutics, and the isolation of known and new compounds has also been reported. Bioactivity studies of extracts and bioguided fractionation to isolate bioactive compounds have also been reported for this plant. Minimal work is reported on this species; however, due to its similarity with each other, data available on different species of genus Tinospora indicate that the species malabarica may also be very prominent as the choice of medicinal compounds and use as raw material in formulation to be used to cure ailments.